Video-electroencephalographic findings and clinical characteristics of bathing seizures in children - Kuang, Xiaojun; Liao, Hongmei; Fang, Hongjun; Zhang, Xiao; Wang, Lijuan; Yang, Liming; Wu, Liwen (Frontiers in Neurology, 2024)
To explore the electroencephalogram (EEG) and clinical characteristics of childhood bathing epilepsy.We conducted a prospective summary of the clinical data from 10 children with bathing epilepsy who were admitted to Hunan Children's Hospital from April 2019 to November 2023 and analyzed their EEGs and clinical characteristics.Our 10 patients included eight males and two females, with seizure-onset ages ranging from 4 months and 20 days to 14 months. Nine cases showed normal intellectual development, and one case manifested delayed development. The Video-EEG (VEEG) findings showed that nine cases exhibited normal background with no interictal epileptic discharge. The seizures were characterized by lip cyanosis, tachycardia or bradycardia, weakness, paleness, and loss of consciousness. Ictal EEG revealed rhythmic fast waves, spike waves, spike-slow waves, or slow and sharp-wave activity over the temporal region (eight cases) or the occipital and temporal regions (one case), finally evolving into a delta rhythm that lasted for 57-201 s. These children exhibited no seizures after discontinuing bathing and were not administered antiseizure medication. The interictal EEG of one case reflected mild slow background and focal interictal epileptic discharge; and her semiology was eyes gazing to right, with clonic movements of the right face and lips, lip cyanosis, bradycardia, and impaired consciousness. Ictal EEG showed spike-wave and spike-slow-wave rhythms over the left central, parietal, and temporal regions; these then spread to the left hemisphere, lasting for approximately 104 s. This patient did not exhibit bathing seizures after stopping her bathing but later experienced frequent spontaneous and drug-resistant seizures. The interictal EEG background slowed down, while focal epileptic discharge increased. Her intellectual development was significantly delayed, and a novel pathogenic mutation in the SMC1A gene, c.298+2T>C, was detected. She was diagnosed with developmental and epileptic encephalopathy.A majority of children with bathing epilepsy in our study showed focal autonomic seizures accompanied by impaired consciousness. Stopping bathing could control the seizures and showed a good prognosis. A few infants manifested a poor prognosis, and we posit that bathing seizure rarely constitute the early manifestations of developmental and epileptic encephalopathy. VEEG findings and clinical features can also indicate the prognosis.